Benzoxazine resin for flexible adhesive-free copper-clad laminate, copper-clad laminate, benzoxazine monomer, and preparation method and application thereof
By using the coordination bond connection between benzoxazine resin and copper foil, the problem of poor heat resistance and weak adhesion at high temperatures is solved, and a copper clad material with high thermal stability, low dielectricity and high reliability is achieved.
Patent Information
- Application Number
- CN202211401360.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-11-09
AI Technical Summary
The existing flexible adhesive-free copper clad plate has poor heat resistance at high temperatures, weak adhesion, and traditional resin materials have high cost and strong structural rigidity, which limits its application.
The benzoxazine resin obtained by ring-open polymerization of benzoxazine monomer is used as a resin coating of the copper clad plate. The bonding performance is improved by connecting with the copper foil, and the dielectric constant and dielectric loss are reduced by introducing a flexible chain.
It improves the thermal stability, adhesion and reliability of copper clad plate, reduces dielectric constant and dielectric loss, enhances insulation performance and dimensional stability, and reduces material costs.
Smart Images

Figure CN115710338B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a benzoxazine resin for a flexible adhesive-free copper-clad laminate, a copper-clad laminate, a benzoxazine monomer, and a preparation method and application thereof. Background Art
[0002] Flexible copper clad laminates are usually divided into two types: three-layer adhesive type and double-layer adhesive-free type. The three-layer adhesive type flexible copper clad laminate is composed of copper foil, soft board adhesive and insulating film. Because it contains an adhesive layer, the process complexity is increased, and when the temperature is higher than 150°C, the peel strength is easily greatly reduced as the adhesive performance is lost. However, when the flexible copper clad laminate is welded, the temperature mostly exceeds 288°C, so the three-layer adhesive type flexible copper clad laminate has poor heat resistance and stability. In addition, the dielectric constant and dielectric loss of the traditional adhesive layer are high, which is not conducive to signal transmission. After being exposed to the air and absorbing moisture, the insulation performance decreases.
[0003] The double-layer adhesive-free flexible copper clad laminate does not contain adhesives and is only composed of copper foil and resin film, so it has better heat resistance, dimensional stability, low water absorption and low dielectric properties. At present, flexible adhesive-free copper clad laminates are mainly made of polyimide resin, but polyimide has high cost, strong structural rigidity and weak adhesion, which limits its application. Summary of the invention
[0004] The purpose of the present application is to provide a benzoxazine resin for a flexible adhesive-free copper clad laminate to improve the reliability, flame retardancy and thermal stability of the copper clad laminate.
[0005] Another object of the present application is to provide a flexible adhesive-free copper clad laminate.
[0006] Another object of the present application is to provide a method for preparing a flexible adhesive-free copper clad laminate.
[0007] Another object of the present application is to provide a benzoxazine monomer.
[0008] Another object of the present application is to provide a method for preparing a benzoxazine monomer.
[0009] Another object of the present application is to provide a benzoxazine resin for a flexible adhesive-free copper-clad laminate, a copper-clad laminate, and an application of a benzoxazine monomer in the field of circuit board preparation.
[0010] To achieve the above objectives, this application provides the following technical solutions:
[0011] In a first aspect, the present application provides a benzoxazine resin for a flexible adhesive-free copper-clad laminate, wherein the benzoxazine resin is obtained by ring-opening polymerization of a monomer having a chemical structure shown in Formula I:
[0012]
[0013] Wherein, R1 is selected from: Any of;
[0014] Wherein R2 is selected from Any of;
[0015] The benzoxazine resin solution has a room temperature viscosity of 10 to 3000 mPa·s.
[0016] Further, in some embodiments of the present application, the T of the benzoxazine resin is g >270℃, tensile strength>140MPa, elastic modulus>2500MPa, elongation at break>10%, heating shrinkage±0.15%, dimensional stability±0.08%, peel strength>0.6kgf / cm, dielectric constant is 2.3-2.6, dielectric loss is 0.002-0.01.
[0017] Furthermore, in some embodiments of the present application, when the benzoxazine resin is used in a flexible adhesive-free copper-clad laminate, part or all of the nitrogen elements are connected to the copper foil of the copper-clad laminate through coordination bonds.
[0018] In a second aspect, the present application also provides a flexible adhesive-free copper-clad laminate, comprising a copper foil and a resin film layer attached to the copper foil;
[0019] The material of the resin film layer is the benzoxazine resin according to any one of claims 1 to 3;
[0020] Part or all of the nitrogen elements in the benzoxazine resin are connected to the copper of the copper foil via coordination bonds.
[0021] Furthermore, in some embodiments of the present application, the thickness of the resin film layer is 10 to 30 μm; and / or
[0022] The copper foil has a thickness of 10 to 35 μm.
[0023] In a third aspect, the present application also provides a method for preparing a flexible adhesive-free copper clad laminate, comprising:
[0024] Provide monomer solution and copper foil;
[0025] The monomer solution is coated on the copper foil, the solvent in the monomer solution is removed, and the monomer is polymerized and cured by heating to obtain a copper clad plate;
[0026] Wherein, the solute of the monomer solution is a monomer as shown in Formula I:
[0027]
[0028] Wherein, R1 is selected from: Any of;
[0029] Wherein R2 is selected from Any of .
[0030] Further, in some embodiments of the present application, heating to polymerize and cure the monomer comprises:
[0031] The monomer is heated at 180-350° C. for 5-500 min to perform ring-opening polymerization and solidification.
[0032] Further, in some embodiments of the present application, removing the solvent in the monomer solution comprises:
[0033] The solvent in the monomer solution is evaporated and removed by heating at 50 to 180° C. for 5 to 500 minutes.
[0034] Further, in some embodiments of the present application, the concentration of the solute in the monomer solution is 5 to 50 wt %;
[0035] The solvent of the monomer solution is selected from one of toluene, xylene, dioxane, butanone, cyclohexanone, dimethylformamide, dichloromethane or chloroform.
[0036] Further, in some embodiments of the present application, providing a monomer solution comprises:
[0037] The monomer solution is obtained by using a phenolic compound, an aldehyde compound and an amine compound to obtain a solute through a dehydration condensation reaction in a solvent;
[0038] Wherein, the phenolic compound is selected from:
[0039] Any of;
[0040] The amine compound is selected from:
[0041] Any of.
[0042] Furthermore, in some embodiments of the present application, the molar ratio of the phenolic compound, the aldehyde compound, and the amine compound is: 2:(4-4.4):1.
[0043] Furthermore, in some embodiments of the present application, the reaction temperature of the dehydration condensation reaction is 40 to 200° C., and the reaction time is 1 to 72 hours.
[0044] In a fourth aspect, the present application further provides a benzoxazine monomer, the chemical structural formula of the benzoxazine monomer is as shown in Formula I:
[0045]
[0046] Wherein, R1 is selected from: Any of;
[0047] Wherein R2 is selected from Any of .
[0048] In a fifth aspect, the present application also provides a method for preparing a benzoxazine monomer, wherein the benzoxazine monomer is obtained by a dehydration condensation reaction of a phenolic compound, an aldehyde compound, and an amine compound;
[0049] Wherein, the phenolic compound is selected from:
[0050] Any of;
[0051] The amine compound is selected from:
[0052] Any of.
[0053] Further, in some embodiments of the present application, the preparation method comprises:
[0054] Providing the phenolic compound, aldehyde compound, amine compound and solvent;
[0055] Adding the phenolic compound, the aldehyde compound, and the amine compound to the solvent in sequence, and mixing them to obtain a reaction system;
[0056] The phenolic compound, the aldehyde compound and the amine compound are dehydrated and condensed at 40 to 200° C. for 1 to 72 hours to obtain a solution of the benzoxazine monomer.
[0057] Further, in some embodiments of the present application, the molar ratio of the phenolic compound, the aldehyde compound, and the amine compound is: 2:(4-4.4):1;
[0058] The content of the solvent in the reaction system is 50 wt % to 95 wt % by mass.
[0059] In a sixth aspect, the present application also provides the use of the benzoxazine resin described in the first aspect or the flexible adhesive-free copper clad laminate described in the second aspect, the flexible adhesive-free copper clad laminate obtained by the preparation method of the flexible adhesive-free copper clad laminate provided in the third aspect, the benzoxazine monomer provided in the fourth aspect, and the benzoxazine monomer prepared by the preparation method of the benzoxazine monomer provided in the fifth aspect in the field of circuit board preparation.
[0060] The present application provides a benzoxazine resin for a flexible non-glue copper-clad laminate, using a benzoxazine resin containing a substituent shown in R1 and R2 as a coating resin for a flexible non-glue copper-clad laminate. Since a flexible chain is introduced into the benzoxazine structure, the benzoxazine resin has a flexible structure, and the flexible chain can also reduce the dielectric constant and dielectric loss, and the nitrogen element in the oxazine ring structure can form a coordination space with copper, thereby enhancing the adhesion between the benzoxazine resin and the copper foil. In addition, the nitrogen element in the oxazine ring structure and the rigid ring in the benzoxazine structure play a flame retardant role, and the rigid ring also provides high heat resistance. Moreover, the volume change of the benzoxazine after curing is small, and the intramolecular hydrogen bond reduces the water absorption rate, providing excellent dimensional stability, insulation and reliability for the insulating layer.
[0061] The present application also provides a kind of flexible glue-free copper-clad laminate, which adopts phenol with specific structure and primary amine and aldehyde compound with specific structure to undergo dehydration condensation reaction in organic solvent to obtain benzoxazine resin as shown in formula I as resin coating, which can be combined with copper foil by coordination bond, and its binding force is strong, which improves the bonding performance of copper foil and resin coating. At the same time, the benzoxazine resin of this structure is used as the resin coating of copper-clad laminate, and its viscosity is moderate, which avoids the defect of poor uniformity of resin coating caused by excessive viscosity, and can also improve the resin coating caused by too low viscosity. It is difficult to reach the required thickness, and can also provide flexibility and good dielectric properties for copper-clad laminate; In addition, benzoxazine resin has lower dielectric constant and dielectric loss performance, lower water absorption, which is conducive to electrical signal transmission and improves the reliability of copper-clad laminate; At the same time, benzoxazine resin also has flame retardancy and higher thermal stability, so that the copper-clad laminate obtained has certain flame retardancy and better thermal stability. In addition, compared with conventional polyimide, benzoxazine resin has low cost, adjustable structure, and can prepare a structure with strong adhesion. Moreover, the solid content of benzoxazine monomer in the solvent can be adjusted in a wide range, which is also conducive to coating control.
[0062] The present application provides a preparation method for a flexible adhesive-free copper-clad laminate. The preparation method is simple and easy to industrialize. The benzoxazine resin with a large concentration adjustment range is used, which is conducive to the process implementation and performance fine-tuning. DETAILED DESCRIPTION
[0063] The following will clearly and completely describe the present application scheme in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0064] In a first aspect, the present application provides a benzoxazine resin for a flexible adhesive-free copper-clad laminate, wherein the benzoxazine resin is obtained by ring-opening polymerization of a monomer having a chemical structure shown in Formula I:
[0065]
[0066] Wherein, R1 is selected from:
[0067] Any of;
[0068] Wherein R2 is selected from Any of .
[0069] The benzoxazine resin solution has a room temperature viscosity of 10 to 3000 mPa·s.
[0070] It should be noted that the viscosity of the benzoxazine resin solution at room temperature in the present application refers to the viscosity of the benzoxazine monomer with a concentration of 5 to 30 wt % provided in the present application measured by a viscometer at a temperature of 25°C.
[0071] In some embodiments, the benzoxazine resin has a T g (Glass transition temperature)>270℃, tensile strength>140MPa, elastic modulus>2500MPa, elongation at break>10%, heating shrinkage±0.15%, dimensional stability±0.08%, peel strength>0.6kgf / cm, dielectric constant is 2.3-2.6, and dielectric loss is 0.002-0.01.
[0072] Benzoxazine resin is a kind of thermosetting resin synthesized from phenol, aldehyde and amine as raw materials. Its cured product has high heat resistance, low dielectric, high modulus, high strength, flame retardancy and low water absorption. It can be used in electronic copper clad laminates, insulation materials, aerospace and adhesives. Flexible copper clad laminates require good flexibility and bonding strength. Currently, they mainly include three-layer adhesive type and double-layer adhesive-free type. Among them, the double-layer adhesive-free flexible copper clad laminate does not require soft board adhesive and solvent, so the structure and process are simpler, and the insulation performance and dielectric properties are better. However, since it has no soft adhesive layer, it has higher requirements for the flexibility of the insulation layer, and the bonding performance of the insulation layer and the copper foil is difficult to meet the requirements. At present, the double-layer adhesive-free flexible copper clad laminate usually adopts the more expensive polyimide resin to meet its flexibility requirements, but its adhesion to the copper foil is still weak, which is difficult to promote and apply, thus hindering the promotion and use of the double-layer adhesive-free flexible copper clad laminate.
[0073] The double-layer non-adhesive flexible copper-clad laminate used in the present application adopts a benzoxazine resin with a long chain structure to improve its flexibility, so that it can be simultaneously applied to high-frequency and high-speed transmission non-adhesive flexible circuit board coatings and used to make insulating base films; at the same time, the nitrogen and oxygen on the benzoxazine resin form coordination bonds with the copper on the copper foil, and there is no need to connect them through adhesives, which can improve the bonding force between the resin and the copper foil, improve the bonding performance, and enable the double-layer non-adhesive flexible copper-clad laminate to be applied to high-frequency and high-speed transmission circuit boards. In addition, the cost of benzoxazine resin is lower, and the insulating base film formed by it has better heat resistance, dimensional stability, low water absorption and low dielectric properties, and is also flame retardant, which is conducive to improving the transmission and reliability of electrical signals in the copper-clad laminate.
[0074] In a second aspect, the present application also provides a flexible adhesive-free copper-clad laminate, comprising a copper foil and a resin film layer attached to the copper foil;
[0075] The material of the resin film layer is the benzoxazine resin described in the first aspect;
[0076] Part or all of the nitrogen elements in the benzoxazine resin are connected to the copper of the copper foil via coordination bonds.
[0077] In some embodiments, the thickness of the resin film layer is 10 to 30 μm; and / or
[0078] The copper foil has a thickness of 10 to 35 μm.
[0079] Among them, the thickness of the resin film layer should not be too high or too low. A too thick resin film layer will exceed the standard and cause waste; an too thin resin film layer will cause surface interference of the substrate, and reduce electrical properties and chemical resistance.
[0080] In a third aspect, the present application also provides a method for preparing a flexible adhesive-free copper clad laminate, comprising:
[0081] Provide monomer solution and copper foil;
[0082] The monomer solution is coated on the copper foil, the solvent in the monomer solution is removed, and the monomer is polymerized and cured by heating to obtain a copper clad plate;
[0083] Wherein, the solute of the monomer solution is a monomer as shown in Formula I:
[0084]
[0085] Wherein, R1 is selected from: Any of;
[0086] Wherein R2 is selected from Any of .
[0087] In some embodiments, heating to polymerize and cure the monomer comprises:
[0088] The monomer is heated at 180-350° C. for 5-500 min to perform ring-opening polymerization and solidification.
[0089] In some embodiments, the temperature for the polymerization and curing of the monomer is further 200-260° C., and the polymerization time is 40-120 min.
[0090] In some embodiments, removing the solvent from the monomer solution comprises:
[0091] The solvent in the monomer solution is evaporated and removed by heating at 50 to 180° C. for 5 to 500 minutes.
[0092] Furthermore, the solvent is heated at 100-160° C. for 5-300 min to be volatilized and removed completely.
[0093] It should be noted that the volatilization temperature of the solvent is lower than the polymerization curing temperature of the benzoxazine resin and higher than the boiling point of the solvent, so that the benzoxazine monomer will not undergo polymerization reaction during this process, and the solvent can also be quickly volatilized and removed.
[0094] In some embodiments, the concentration of the solute in the monomer solution is 5 to 50 wt %;
[0095] The solvent of the monomer solution is selected from one of toluene, xylene, dioxane, butanone, cyclohexanone, dimethylformamide, dichloromethane or chloroform. The solvent is further selected from toluene or butanone because the solvent has good solubility for benzoxazine and a low boiling point, and is easy to remove.
[0096] In some embodiments, the concentration of the solute in the monomer solution is 5 to 30 wt %, so that the viscosity of the resulting reaction system can be in the range of 10 to 3000 mPa·s at room temperature, which is more suitable for coating.
[0097] It should be noted that the concentration of the solute in the monomer solution, ie, the benzoxazine monomer, can be finely adjusted as needed, so that the performance of the resulting resin film (insulating base film) is more in line with the performance requirements of the copper clad laminate.
[0098] In some embodiments, providing a monomer solution comprises:
[0099] The monomer solution is obtained by using a phenolic compound, an aldehyde compound and an amine compound to obtain a solute through a dehydration condensation reaction in a solvent;
[0100] Wherein, the phenolic compound is selected from:
[0101]
[0102] Any of;
[0103] The amine compound is selected from:
[0104] Any of.
[0105] In some embodiments, the molar ratio of the phenolic compound, the aldehyde compound, and the amine compound is 2:(4-4.4):1.
[0106] In some embodiments, the reaction temperature of the dehydration condensation reaction is 40-200° C., and the reaction time is 1-72 hours; further, the reaction temperature of the dehydration condensation reaction is 60-150° C., and the reaction time is 8-24 hours.
[0107] In the present application, the benzoxazine monomer is obtained by dehydration condensation of phenols, aldehydes and amine compounds, and the general reaction formula thereof can be:
[0108]
[0109] Wherein, the aldehyde compound may be: formaldehyde, paraformaldehyde.
[0110] In a fourth aspect, the present application further provides a benzoxazine monomer, the chemical structural formula of the benzoxazine monomer is as shown in Formula I:
[0111]
[0112] Wherein, R1 is selected from: Any of;
[0113] Wherein R2 is selected from Any of .
[0114] In a fifth aspect, the present application also provides a method for preparing a benzoxazine monomer, wherein the benzoxazine monomer is obtained by a dehydration condensation reaction of a phenolic compound, an aldehyde compound, and an amine compound;
[0115] Wherein, the phenolic compound is selected from:
[0116]
[0117] Any of;
[0118] The amine compound is selected from:
[0119] Any of.
[0120] In some embodiments, the preparation method comprises:
[0121] Providing the phenolic compound, aldehyde compound, amine compound and solvent;
[0122] Adding the phenolic compound, the aldehyde compound, and the amine compound to the solvent in sequence, and mixing them to obtain a reaction system;
[0123] The phenolic compound, the aldehyde compound and the amine compound are dehydrated and condensed at 40 to 200° C. for 1 to 72 hours to obtain a solution of the benzoxazine monomer.
[0124] In some embodiments, the molar ratio of the phenolic compound, the aldehyde compound, and the amine compound is: 2:(4-4.4):1;
[0125] The content of the solvent in the reaction system is 50 wt % to 95 wt % by mass.
[0126] In a sixth aspect, the present application also provides the use of the benzoxazine resin described in the first aspect or the flexible adhesive-free copper clad laminate described in the second aspect, the flexible adhesive-free copper clad laminate obtained by the preparation method of the flexible adhesive-free copper clad laminate provided in the third aspect, the benzoxazine monomer provided in the fourth aspect, and the benzoxazine monomer prepared by the preparation method of the benzoxazine monomer provided in the fifth aspect in the field of circuit board preparation.
[0127] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0128] The 4-butylphenol used in the following specific examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0129] The 4,4-diaminodiphenylmethane used in the following specific examples was obtained from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0130] The paraformaldehyde used in the following specific examples was purchased from Chengdu Kelong Chemical Co., Ltd.;
[0131] The p-allylphenol used in the following specific examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0132] The p-tert-butylphenol used in the following specific examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0133] The 4-(tert-butyldimethylsilyloxy)phenol used in the following specific examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0134] The toluene used in the following specific examples was purchased from Chengdu Kelong Chemicals Co., Ltd.
[0135] Example 1
[0136] 4-Butylphenol (1.202 g, 0.008 mol) and 4,4-diaminodiphenylmethane (0.793 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0137] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0138] Example 2
[0139] p-Allylphenol (1.073 g, 0.008 mol) and 4,4-diaminodiphenylmethane (0.793 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0140] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0141] Example 3
[0142] 4-tert-Butylphenol (1.202 g, 0.008 mol) and 4,4-diaminodiphenylmethane (0.793 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0143] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0144] Example 4
[0145] 4-(tert-butyldimethylsilyloxy)phenol (1.795 g, 0.008 mol) and 4,4-diaminodiphenylmethane (0.793 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0146] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0147] Example 5
[0148] 4-Butylphenol (1.202 g, 0.008 mol) and 4,4-diaminodiphenyl ether (0.8 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0149] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0150] Example 6
[0151] p-Allylphenol (1.073 g, 0.008 mol) and 4,4-diaminodiphenyl ether (0.8 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0152] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0153] Example 7
[0154] 4-tert-Butylphenol (1.202 g, 0.008 mol) and 4,4-diaminodiphenyl ether (0.8 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0155] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0156] Example 8
[0157] 4-(tert-butyldimethylsilyloxy)phenol (1.795 g, 0.008 mol) and 4,4-diaminodiphenyl ether (0.8 g, 0.004 mol) were added to toluene (10 g) and stirred at room temperature to dissolve the solid. Paraformaldehyde (0.48 g, 0.016 mol) was added and stirred at room temperature for 24 hours to form a benzoxazine solution.
[0158] After the benzoxazine solution was saliva coated on the surface of the copper foil, it was placed in a vacuum oven at 110°C for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240°C in a nitrogen-protected oven and kept for 60 minutes for thermal curing to obtain a benzoxazine flexible adhesive-free copper clad laminate.
[0159] Comparative Example 1
[0160] 2 g of commercially available polyimide powder was added to N-methylpyrrolidone (10 g), and the solid was dissolved by stirring at room temperature to form a polyimide solution. The polyimide solution was coated on the surface of the copper foil, and then placed in a vacuum oven at 110° C. for 240 minutes to remove the organic solvent. Then, it was slowly heated to 240° C. in a nitrogen-protected oven and maintained for 60 minutes for heat treatment to obtain a comparative polyimide flexible non-glue copper-clad laminate 1.
[0161] Comparative Example 2
[0162] Compared with Example 1, this comparative example uses bisphenol A to replace 4-butylphenol, and the other steps are the same as those of Example 1 to obtain a comparative benzoxazine flexible adhesive-free copper clad laminate 2.
[0163] Comparative Example 3
[0164] Compared with Example 1, this comparative example uses aniline to replace 4,4-diaminodiphenylmethane, and the other steps are the same as those in Example 1, to obtain a comparative benzoxazine flexible adhesive-free copper clad laminate 3.
[0165] The properties of the benzoxazine flexible adhesive-free copper-clad laminates obtained in Examples 1 to 8 and Comparative Examples 1 to 3 were tested.
[0166] Peel strength: AGS-J peel strength test (Shimadzu Corporation) was used in accordance with IPC-TM6502.4.9 standard.
[0167] Solder resistance: soldering furnace (Shenzhen Fujite), in accordance with IPC-TM6502.4.13 standard.
[0168] Water absorption rate: dry at 105-110℃ for 1h, immerse in water at 23±1.1℃ for 24+0.5h, and weigh and test
[0169] Dielectric constant and dielectric loss, N5232A (Agilent), in accordance with IPC-TM6502.5.5.3 standard.
[0170] Dimensional stability: TMAQ400 (American TA) in accordance with IPC-TM6502.4.4 standard.
[0171] Elongation at break: AGS-J (Shimadzu Corporation) was used in accordance with IPC-TM6502.4.3 standard.
[0172] The test results are shown in Table 1, which shows the properties of the flexible adhesive-free copper clad laminates obtained in Examples 1 to 8 and Comparative Examples 1 to 3.
[0173] Table 1
[0174]
[0175] It can be seen from the performance test table that the flexible adhesive-free copper clad laminate prepared by benzoxazine has excellent performance, low water absorption, good stability. At the same time, the dielectric constant and dielectric loss are low, and it can be used in high-frequency and high-speed fields.
[0176] By comparing the comparative examples, it can be seen that the benzoxazine prepared by using phenol or amine of other structures has a higher dielectric constant due to its lack of flexible connection. In addition, the flexible copper clad laminate comparative example 1 prepared by using commercially available polyimide powder has low peel strength and high dielectric constant. It can be seen that the type of benzoxazine prepared by the present invention can be effectively applied to flexible adhesive-free copper clad laminates.
[0177] The description of the above embodiments 1-8 is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principle of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A benzoxazine resin for flexible adhesive-free copper-clad laminate, characterized in that: The benzoxazine resin is obtained by ring-opening polymerization of a monomer having a chemical structure as shown in Formula I: Wherein, R1 is selected from: , , , , , , , , , , , , , Any of; Wherein R2 is selected from , , , , Any of; The room temperature viscosity of the benzoxazine resin solution is 10-3000 mPa·s.
2. The benzoxazine resin for flexible adhesive-free copper clad laminate according to claim 1, characterized in that: The T of the benzoxazine resin g >270℃, tensile strength>140MPa, elastic modulus>2500MPa, elongation at break>10%, heating shrinkage±0.15%, dimensional stability±0.08%, peel strength>0.6kgf / cm, dielectric constant is 2.3-2.6, dielectric loss is 0.002-0.
01.
3. The benzoxazine resin for flexible adhesive-free copper clad laminate according to claim 1, characterized in that: When the benzoxazine resin is used in a flexible adhesive-free copper-clad laminate, part or all of the nitrogen elements are connected to the copper foil of the copper-clad laminate through coordination bonds.
4. A flexible adhesive-free copper-clad laminate, characterized in that: It includes a copper foil and a resin film layer attached to the copper foil; The material of the resin film layer is the benzoxazine resin according to any one of claims 1 to 3; Part or all of the nitrogen elements in the benzoxazine resin are connected to the copper of the copper foil via coordination bonds.
5. The flexible adhesive-free copper-clad laminate according to claim 4, characterized in that: The thickness of the resin film layer is 10-30 μm; and / or The copper foil has a thickness of 10-35 μm.
6. A method for preparing a flexible adhesive-free copper-clad laminate, characterized in that: include: Provide monomer solution and copper foil; The monomer solution is coated on the copper foil, the solvent in the monomer solution is removed, and the monomer in the monomer solution is polymerized and solidified by heating to obtain a copper clad plate; Wherein, the monomer in the monomer solution is a monomer as shown in Formula I: Wherein, R1 is selected from: , , , , , , , , , , , , , Any of; Wherein R2 is selected from , , , , Any of .
7. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 6, characterized in that: Heating the monomers in the monomer solution to polymerize and solidify the monomers comprises: The monomer is heated at 180-350° C. for 5-500 min to perform ring-opening polymerization and solidification.
8. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 6, characterized in that: Removing the solvent from the monomer solution comprises: The solvent in the monomer solution is evaporated and removed by heating at 50-180° C. for 5-500 min.
9. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 6, characterized in that: The concentration of the monomer in the monomer solution is 5-50wt%; The solvent of the monomer solution is selected from one of toluene, xylene, dioxane, butanone, cyclohexanone, dimethylformamide, dichloromethane or chloroform.
10. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 6, characterized in that: Providing a monomer solution comprises: The monomer solution is obtained by using a phenolic compound, an aldehyde compound and an amine compound to obtain a solute through a dehydration condensation reaction in a solvent; Wherein, the phenolic compound is selected from: , , , , , , , , , , , , , , Any of; The amine compound is selected from: , , , , Any of .
11. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 10, characterized in that: The molar ratio of the phenolic compound, the aldehyde compound and the amine compound is: 2:(4-4.4):
1.
12. The method for preparing the flexible adhesive-free copper-clad laminate according to claim 10, characterized in that: The reaction temperature of the dehydration condensation reaction is 40-200° C., and the reaction time is 1-72 hours.
13. A benzoxazine monomer, characterized in that: The chemical structural formula of the benzoxazine monomer is shown in Formula I: Wherein, R1 is selected from: , , , , , , , , , , , , , Any of; Wherein R2 is selected from , , , , Any of .
14. A method for preparing a benzoxazine monomer, characterized in that: The benzoxazine monomer is obtained by dehydration condensation reaction of phenolic compounds, aldehyde compounds and amine compounds; Wherein, the phenolic compound is selected from: , , , , , , , , , , , , , , Any of; The amine compound is selected from: , , , , Any of .
15. The method for preparing a benzoxazine monomer according to claim 14, characterized in that: include: Providing phenolic compounds, aldehyde compounds, amine compounds and solvents; Adding the phenolic compound, the aldehyde compound, and the amine compound to the solvent in sequence, and mixing them to obtain a reaction system; The phenolic compound, the aldehyde compound and the amine compound are dehydrated and condensed at 40-200° C. for 1-72 hours to obtain a solution of the benzoxazine monomer.
16. The method for preparing a benzoxazine monomer according to claim 15, characterized in that: The molar ratio of the phenolic compound, the aldehyde compound and the amine compound is: 2:(4-4.4):1; The content of the solvent in the reaction system is 50 wt % to 95 wt % by mass.
17. Use of the benzoxazine resin according to any one of claims 1 to 3, the flexible adhesive-free copper-clad laminate according to any one of claims 4 to 5, the flexible adhesive-free copper-clad laminate obtained by the preparation method of any one of claims 6 to 12, the benzoxazine monomer according to claim 13, or the benzoxazine monomer prepared by the preparation method of the benzoxazine monomer according to any one of claims 14 to 16 in the field of circuit board preparation.
Citation Information
Patent Citations
Heterocyclic compound containing nitrogen and oxygen and manufacturing method thereof
TW200526648A
Azaoxa heterocyclic compound and method of preparing the same
US20040068084A1